Combating the common enemy? A descriptive account of Namiba's involvement in the Angolan civil conflict (Journal for Studies in Humanities and Social Sciences, 2019)
Although there are several studies on post-colonial Namibia, the subject of Namibia’s foreign relations in general and military operations in particular has not attracted many studies by local scholars. This subject has been left either for exploration by foreign scholarship or to local journalists to provide somewhat ‘pass-by’ accounts. There is thus little literature available on the subject such as the role of Namibia in the Angolan civil conflict. This reason alone is sufficient to make a compelling case on why there is a need for an account on the role of Namibia in this conflict. Produced on account of necessity, it is the hope of this author that it serves as a foundation for further research; regardless of the perspective – for or against, as long as studies on the subject exist. Most of the studies on conflict resolution and peacemaking are often focused on colonialism as if Namibia and generally southern Africa did not witness more than 20 years of post-colonial majority rule. This article seeks to explain the contours of conflict studies from colonial to post-colonial period.